Transcription factors in megakaryocytes and platelets - Yuan, Hengjie; Liu, Yafan; Zhang, Jianning; Dong, Jing-fei; Zhao, Zilong (Frontiers in Immunology, 2023)
Transcription factors bind promoter or regulatory sequences of a gene to regulate its rate of transcription. However, they are also detected in anucleated platelets. The transcription factors RUNX1, GATA1, STAT3, NFκB, and PPAR have been widely reported to play key roles in the pathophysiology of platelet hyper-reactivity, thrombosis, and atherosclerosis. These non-transcriptional activities are independent of gene transcription or protein synthesis but their underlying mechanisms of action remain poorly defined. Genetic and acquired defects in these transcription factors are associated with the production of platelet microvesicles that are known to initiate and propagate coagulation and to promote thrombosis. In this review, we summarize recent developments in the study of transcription factors in platelet generation, reactivity, and production of microvesicles, with a focus on non-transcriptional activities of selected transcription factors.